Pengaruh Paparan Film Petaka Gunung Gede 2025 terhadap Sikap dan Niat Porter dan Guide Rineh Adventure dalam Mematuhi Larangan Mendaki saat Menstruasi - Andihka . (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
This study aims to analyze the effect of exposure to the film Petaka Gunung Gede 2025 on the Attitude (Y1) and Intention (Y2) of Rineh Adventure porters and guides in complying with the prohibition of climbing during menstruation. The study used an explanatory quantitative approach with a questionnaire. The study population was 137 people and the sample was calculated using the Slovin formula (e = 5%) resulting in 103 respondents, consisting of 88 porters and 15 guides. Data were collected through a Likert scale questionnaire and analyzed using simple linear regression (t-test). The results of the analysis showed that film exposure had a significant effect on attitudes (t = 27.775; Sig. <0.001) with a contribution of 88.4% (R² = 0.884). Film exposure also had a significant effect on intention (t = 29.202; Sig. < 0.001) with a contribution of 89.4% (R² = 0.894). Film exposure also had a significant effect on intentions (Sig. <0.001) with a contribution of 89.4% (R² = 0.894). Furthermore, attitude significantly influenced intention (t = 27.885; Sig. < 0.001), contributing 88.5% (R² = 0.885). This finding confirms that film can serve as a medium for education/risk communication related to attitude formation and strengthening compliance intentions among field actors.